Celulose de SCOBY aplicada a indústria de alimentos: alternativa na obtenção e métodos de purificação - Fernandes, Laylla Nunes (2023)
This study aimed to relate the benefits, uses and limitations of vegetable, bacterial and SCOBY cellulose in the food industry, focusing on obtaining and applying SCOBY cellulose (CS) as a food raw material and its use in the reuse of food waste. The research involved a comprehensive review of scientific literature, focusing on data from the last 10 years, obtained through search bases such as Elsevier and Science Direct, with pertinent keywords such as alkalization, foods, cellulose, bacterial cellulose, co-products, kombucha, NaOH, purification and SCOBY. The research highlighted the importance of cellulose in the food industry as a sustainable alternative for reducing additives, sodium and fat, as well as improving the sensory properties of final products, and its use as a reinforcing material in active packaging. The literature highlighted SCOBY cellulose (CS) as a cheap and alternative raw material to be explored in the production of commercial bacterial cellulose and in the development of new products. However, treatment techniques applied to SCOBY fibers are still in the early stages of development, lacking standardization and optimal efficiency, which constitutes a significant challenge for their large-scale adoption. In this context, there is a pressing need for additional research aimed at optimizing the processes for obtaining and purifying SCOBY cellulose. Despite technical limitations, SCOBY cellulose presents considerable economic advantages, due to its availability in the production of kombucha and the possibility of using the fermentative culture, SCOBY, in fermentations of different substrates, such as Camellia sinensis, co-products of the acerola production chain and from wineries, for example, and food waste, as a source of culture medium for cellulose-producing bacteria. This versatility suggests significant potential for developing new food products and reducing industrial waste, in conjunction with obtaining bacterial cellulose. To purify SCOBY cellulose and other forms of cellulose, physical, chemical and/or enzymatic treatments are necessary in order to remove impurities and make it more suitable for various applications. In this sense, sodium hydroxide emerges as the most used product for the purification of bacterial cellulose and SCOBY, as indicated in the reviewed literature. This study contributed to the understanding of the potential of SCOBY cellulose in the food industry and highlights key areas for future research, aiming to improve